2012
DOI: 10.1111/j.1758-0854.2012.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Psychology's Role in Peptic Ulcer

Abstract: This paper reviews the history of the transition from the belief that gastrointestinal ulcers are caused primarily by psychological factors to the current state of belief that they are caused primarily by infection and argues that neither is fully accurate. We argue that psychological factors play a significant role as predisposing to vulnerability, modulating of precipitation, and sustaining of gastric ulceration. We review data that challenge the assumption of a simple infectious disease model and adduce rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 77 publications
0
16
0
1
Order By: Relevance
“…Earlier research suggested that stress was a causal factor in gastrointestinal ulcer development [1, 2], but the subsequent discovery of the causal role of the Helicobacter pylori bacterium sharply diminished interest in stress-related ulcer research[1, 3, 4]. Although further research has established that H-pylori is neither a sufficient nor necessary cause of peptic ulcer [2, 3, 5], interest in stress and other psychological factors in ulcer development has not recovered [6].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research suggested that stress was a causal factor in gastrointestinal ulcer development [1, 2], but the subsequent discovery of the causal role of the Helicobacter pylori bacterium sharply diminished interest in stress-related ulcer research[1, 3, 4]. Although further research has established that H-pylori is neither a sufficient nor necessary cause of peptic ulcer [2, 3, 5], interest in stress and other psychological factors in ulcer development has not recovered [6].…”
Section: Introductionmentioning
confidence: 99%
“…Poor stress resilience, and therefore stress, may increase the likelihood of behaviours and characteristics that in turn increase PUD risk. 4 Even though our study had no data on smoking, we did adjust for a measure of inflammation (ESR) in adolescence that has been linked with smoking although not always consistently. 25,[32][33][34][35] Cognitive function (and education) is strongly related to behaviours such as smoking, 36, 37 so we adjusted for this.…”
Section: 4mentioning
confidence: 99%
“…[2][3][4][5][6] Despite this, recent studies indicate that stress may still be relevant to the risk and course of PUD. 2,4,6,7 However, inconsistent results and potential methodological limitations warrant further research. Stressful life events have been associated with increased PUD risk in some studies, 2, 7-10 but others did not find this.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations